Implementation of Data Mining Teacher Performance Assessment Using the K-means Clustering Method in Student Learning Styles in the 4.0 Era - Zul'Aini, Nurul Hasanah; Lubis, Imran; Ria Pasaribu, Tio (Journal of Engineering, Technology and Computing (JETCom), 2024)
In today's digital era, information technology has changed various aspects of life, including in the world of education. Era 4.0 provides new challenges for education, including in assessing teacher performance. Teacher performance evaluation is an important aspect in improving the quality of education. However, in measuring teacher performance, there are many factors to consider, including student learning styles. This research was conducted at the Paba Binjai school by conducting direct interviews with 700 students who would fill out questionnaire data. This method is a popular method used in cluster analysis, which aims to group data into several homogeneous groups based on the similarity of the attributes possessed. there are 4 data and group 3 there are 6 data. The explanation of the 3 groups is as follows: 1. Cluster 1 There are 12 data 6.4 1.9 1.6 Based on the above calculations it can be seen that in cluster 1 the teacher performance assessment data in the learning styles of SMK Paba Binjai students in the Subject group ( X) is Computer and Network Engineering, for the Student Evaluation Learning group (Y) is Achieved, and in the Learning Style group (Z) is Auditory. 2. Cluster 2 There are 4 data 7.75 2.5 1.5 Based on the above calculations it can be seen that in cluster 2 the data on teacher performance assessment in the learning styles of Paba Binjai Vocational High School students in the Subject group (X) is Software Engineering, for the group Student evaluation (Y) is quite achieved, and in the learning style group (Z) is auditory. 3. Cluster 3 There are 6 data 6.5 1.5 1.6 Based on the above calculations it can be seen that in cluster 3 the teacher performance assessment data in the learning styles of Paba Binjai Vocational High School students in the Subject group (X) are Computer and Network Engineering, for the student evaluation group (Y) is achieved, and in the learning style group (Z) enough is auditory. This assessment is used as a consideration for school principals in deciding teachers who lack integrity and produce a group of teachers who have very good, good, moderate, and poor teaching quality.